The porn trap : the essential guide to overcoming problems caused by pornography - Maltz, Wendy; Maltz, Larry (New York : Harper, 2010)
This volume examines porn addiction and other devastating consequences of porn use, addressing the full range of problems that impact everyone from recreational "dabblers" to compulsive addicts, and the people who care about them. The authors shed new light on the power of pornography -- revealing why it's so easy to develop a serious problem with porn and often hard to break free from porn's clutches. They offer a practical approach for healing supported by innovative exercises, checklists, and suggestions that will help readers identify and evaluate the impact of porn; decide whether it's time to quit using porn; learn how to stop using porn and deal with cravings; rebuild self-esteem and restore personal integrity; heal a relationship harmed by porn use; and develop a thriving and satisfying sexual life without porn.
pt. 1: Becoming aware. The hidden power of porn -- First encounters -- The porn relationship -- To see or not to see-the consequences of porn -- Partners in pain -- Hitting bottom -- pt. 2: Healing. Getting motivated to quit porn -- Six basic action steps -- Handling and preventing relapses -- Healing as a couple -- A new approach to sex -- True freedom and fulfillment.
Originally published: 2008.
Includes bibliographical references and index.
Keywords: Pornography; Sex addiction; Sex addicts -- Rehabilitation